Auditor lobbying on accounting standards - Allen, A; Ramanna, K; Roychowdhury, S (Now Publishers, 2018)
We examine how Big N auditors’ changing incentives impact their comment-letter lobbying on U.S. GAAP over the first thirty-four years of the FASB (1973–2006). In particular, we focus on the influence of auditors’ lobbying incentives arising from two basic factors: managing expected litigation and regulatory costs and catering to clients’ preferences for flexibility in GAAP. We find evidence that auditor lobbying is driven by prevailing standards of litigation and regulatory scrutiny, but we find no evidence that catering to clients’ preferences for flexibility in GAAP drives auditor lobbying. Broadly, our paper offers the first large-sample descriptive analysis of the role of Big N auditors in the accounting standard-setting process.